2008
DOI: 10.1099/vir.0.2008/001925-0
|View full text |Cite
|
Sign up to set email alerts
|

Four novel human betapapillomaviruses of species 2 preferentially found in actinic keratosis

Abstract: Recent studies have suggested an association between human papillomaviruses (HPVs), particularly species 2 members of the genus Betapapillomavirus, and squamous cell carcinoma (SCC) of the skin. As most of these viruses are uncharacterized, molecular characterization and epidemiology are needed to advance our understanding of their significance in carcinogenesis. This study determined the complete genomes of four betapapillomaviruses of species 2 from skin lesions designated , an isolate of an unpublished HPV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
48
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 42 publications
2
48
0
Order By: Relevance
“…HPV is known to be very commonly present in SCC but usually in very low amounts of virus (38)(39)(40). This is in line with our findings that MDA commonly amplifies S. aureus but only occasionally (a single tumor) amplifies HPV in SCC specimens.…”
Section: Discussionsupporting
confidence: 81%
“…HPV is known to be very commonly present in SCC but usually in very low amounts of virus (38)(39)(40). This is in line with our findings that MDA commonly amplifies S. aureus but only occasionally (a single tumor) amplifies HPV in SCC specimens.…”
Section: Discussionsupporting
confidence: 81%
“…The sequence of HPV 100 L1 is 79 % identical to the L1 ORFs of both HPV 22 and HPV 23. The HPV 104 ORF L1 nucleotide sequence is 78 % identical to that of HPV 107, and the HPV 113 ORF L1 nucleotide sequence is 83 % identical to that of HPV 111 (Vasiljevic et al, 2008) and 78 % identical to that of HPV 9. (94) 82 (89) 79 (86) 79 (87) 78 (85) 80 (86) 83 (92) L2 88 (91) 79 (86) 82 (90) 74 (72) 71 (70) 77 (85) 77 (86) 83 (90) E1 91 (92) 83 (83) 87 (88) 83 (82) 83 (81) 80 (81) 85 (87) 86 (88) E2 91 (89) 75 (80) 80 (76) 75 (76) 78 (85) 74 (73) 72 (71) 88 (86) E6 90 (88) 85 (88) 81 (81) 76 (79) 79 (79) 75 (75) 78 (73) 84 (86) E7 95 (94) 87 (89) 85 (81) 84 (82) 79 (74) 79 (78) 83 (86) 90 (96) *E6 uses the second ATG.…”
mentioning
confidence: 96%
“…Several subsequent studies attempted to associate specific HPV types with the aetiology of non-melanoma skin cancer in immunosuppressed and immunocompetent patients (Shamanin et al, 1994(Shamanin et al, , 1996 Berkhout et al, 1995Berkhout et al, , 2000de Villiers et al, 1997;Forslund et al, 1999Forslund et al, , 2003bForslund et al, , 2007Asgari et al, 2008;Harwood et al, 2000Harwood et al, , 2004, whereas others demonstrated the presence of HPV in and on normal skin (Astori et al, 1998;Antonsson et al, 2000;Hazard et al, 2007;Chen et al, 2008). These studies all resulted in the identification of a vast spectrum of additional putative novel HPV types in the form of PCRamplified partial open reading frame (ORF) L1 sequences (Shamanin et al, 1996;de Villiers et al, 1997; Astori et al, 1998;Antonsson et al, 2000;Forslund et al, 2003a;.Full-length genomes of a relatively small number of these HPV isolates have been cloned and characterized (Delius et al, 1998;Forslund et al, 2003a;Vasiljevic et al, 2007Vasiljevic et al, , 2008. Definition of a papillomavirus type requires the isolation and characterization of a full-length genome in order to verify the genome organization characteristic of papillomaviruses (de Villiers et al, 2004a).…”
mentioning
confidence: 99%
See 2 more Smart Citations